LOW-INTENSITY PULSED ULTRASOUND PROMOTES CHONDROGENIC PROGENITOR CELL MIGRATION VIA FOCAL ADHESION KINASE PATHWAY - Jang, Kee W. (2014)
Low-intensity pulsed ultrasound (LIPUS) has been frequently studied for its beneficial effects on the repair of injured articular cartilage. Here, we hypothesized that these effects are due to stimulation of chondrogenic progenitor cell (CPC) migration toward injured areas in cartilage through focal adhesion kinase (FAK) activation. CPC chemotaxis in bluntly impacted osteochondral explants was examined by confocal microscopy and migratory activity of cultured CPCs was measured in trans-well and monolayer scratch assays. FAK activation by LIPUS was analyzed in cultured CPCs by western blot. LIPUS effects were compared with the effects of two known chemotactic factors; formylated-methionine peptides (fMLF), and high-mobility group box 1 (HMGB1) protein. LIPUS significantly enhanced CPC migration on explants and in cell culture assays. Phosphorylation of FAK at the kinase domain (Tyr 576/577) was maximized by 5 minute exposure to LIPUS at a dose of 27.5 mW/cm(2) and at a frequency of 3.5 MHz. Treatment with fMLF, but not HMBG1 enhanced FAK activation to a degree similar to LIPUS, but neither fMLF nor HMGB1 enhanced the LIPUS effect. LIPUS-induced CPC migration was blocked by suppressing FAK phosphorylation with a Src family kinases (SFKs) inhibitor that blocks FAK phosphorylation. Our results imply that LIPUS might be utilized to promote cartilage healing by inducing the migration of CPCs to injured sites, which could delay or prevent the onset of post-traumatic osteoarthritis (PTOA).